Climate change, vulnerability and migration - Irudaya Rajan, S.; Bhagat, R. B. (New York : Routledge, 2018)
Contributed articles on the climate changes and migration challenegs in india presented at 'National Workshop on Migration and Global Environmental Change in India" 4-5 March 2014 at New Delhi organised by UNESCO New Delhi and Foresight, United Kingdom ; some papers are also from International Seminar on 'Migration, Care Economy, and Development' organized at Centre for Development Studies, Thiruvananthapuram, Kerala.
Includes bibliographical references and index.
Keywords: Climatic changes -- India -- Congresses; Migration, Internal -- India -- Congresses